Instructional Model Using Simulation-Based Learning on Knowledge Self-Confidence and Practical Skills of Nursing Students Concerning Basic Surgical Procedures - Maneewong, Supranee; Naktes, Chainarong; Puengsema, Ratana; Rungrojwattana, Wassana (Journal of health and health management, 2023)
This quasi-experimental research aimed to examine an instructional model by using simulation-based learning to assess the knowledge, self-confidence and practical skills of nursing students relating to basic surgical procedures. The sample comprised 64 senior nursing students who were divided equally into an experimental group (n = 32) and a comparison group (n = 32) by systematic random sampling. The instructional model created by the researcher consisted of simulation-based learning, video clips, case-based learning and technical skills training pertaining to basic surgical procedures. Data were collected by questionnaires that measured knowledge, self-confidence and technical skills of basic surgical procedures. Data were analysed using independent t-test and one-way repeated measure ANOVA. The results revealed that the intervention group had significantly higher mean scores for the knowledge of basic surgical procedures, self-confidence in basic surgical procedures, and technical skills in basic surgical procedures after the intervention than before the intervention and compared to those in the comparison group (p < .05). Further, these results were sustainable in the follow-up period. The instructional model using simulation-based learning should be applied to prepare nursing practicum in clinics by emphasising the creation of a learning environment with innovative experiences through the use of simulations that are similar to real-life situations.